Analisis Komunikasi Matematis Dalam Menyelesaikan Soal Materi Operasi Bilangan Bulat - Oktavia, Zulva; Dimas Anditha Cahyo Sujiwo; Anas, Aswar (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
The purpose of this study was to describe students' mathematical communication skills in solving problems involving integer operations. Mathematical communication is the effective delivery of ideas, understanding, and mathematical concepts between individuals, covering various aspects, including the use of symbols, language, and graphics to explain mathematical concepts and solutions. This research method uses a qualitative method. The results of the study showed that two highly capable subjects were able to complete well according to what was instructed according to the mathematical communication indicators, namely written text, drawing, and mathematical expression. Based on interviews, both subjects were able to explain according to what was done (each student's answer). While low-ability subjects completed well according to what was instructed according to the mathematical communication indicators, namely written text and mathematical expression, both subjects were unable to meet the drawing indicator. Based on interviews, both subjects were able to explain according to what was done (each student's answer) on two mathematical communication indicators, namely written text and mathematical expression, but were unable to explain on the drawing indicator. Keywords: integers, mathematical communication, solving problems